2013
DOI: 10.1002/jsfa.6212
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of soybean by‐product okara and inulin in a probiotic soy yoghurt: texture profile and sensory acceptance

Abstract: The results showed that the addition of okara flour and the storage were significant factors to increase firmness of the soy yoghurts. SY acceptability was not affected by the incorporation of inulin or okara. These results suggest that okara, discarded as industrial waste, may be used in probiotic soy yoghurt, helping to increase the nutritional and functional properties without altering its acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
3
25
1
Order By: Relevance
“…Though this concept seems logical, it is not widely applied. For example, a recent study on the production of soy yoghurt from soy milk reported on the addition of okara, a by-product of soy milk production was added to increase nutritional content (Bedani et al, 2014). Following the concept above, it would be better to extract all components necessary from the soy beans directly instead of separating those and combining them in the final application as proposed by the paper mentioned.…”
Section: Towards a New Process Chain Designmentioning
confidence: 94%
“…Though this concept seems logical, it is not widely applied. For example, a recent study on the production of soy yoghurt from soy milk reported on the addition of okara, a by-product of soy milk production was added to increase nutritional content (Bedani et al, 2014). Following the concept above, it would be better to extract all components necessary from the soy beans directly instead of separating those and combining them in the final application as proposed by the paper mentioned.…”
Section: Towards a New Process Chain Designmentioning
confidence: 94%
“…An increased consumer desire for a healthy lifestyle has resulted in demands from the bakery industry for breads containing functional compounds. There is an immediate requirement for the food industry to prepare healthy bakery products to satisfy consumers' health needs [13], [14], [15]. Thus through this project, the importance of millets fortified with different nutritional ingredients have been explored.…”
Section: Resultsmentioning
confidence: 99%
“…Wang The addition of inulin did not affect the adhesiveness of probiotic yoghurts, since there were no significant differences between the control yoghurt and yoghurts supplemented with inulin. In another study, the addition of inulin did not affect either firmness or adhesiveness of probiotic soy yoghurt during 28 days of storage (Bedani et al, 2014). It has been suggested that inulin is a waterstructuring agent, and may form a complex with protein aggregates in yoghurts, which could explain the increase in firmness in these products (Kip et al, 2006).…”
Section: Textural Propertiesmentioning
confidence: 97%
“…Similar decreases were also detected for texture and overall acceptability values of sample with 2 % Himaize. Bedani et al (2014) also noted a statistically important reduction in sensory acceptability scores for control probiotic soy yoghurt and the sample supplemented with inulin on the 21 st day of storage.…”
Section: Sensory Characteristicsmentioning
confidence: 99%